(untitled) (International journal of artificial intelligence, 2024)
This article provides a comprehensive overview of various teaching methods employed in English as a Second Language (ESL) education. It explores the evolution of these methods, their key principles, strengths, and limitations, and how they cater to different learning styles and educational contexts. The article emphasizes the importance of a learner-centered approach, incorporating diverse strategies and technologies to effectively facilitate language acquisition.